Temperature and water content influence on thermophysical properties of coffee extract - Telis-Romero, J.; Gabas, A. L.; Polizelli, M. A.; Telis, VRN (Marcel Dekker Inc, 2000)
Specific heat, thermal conductivity, thermal diffusivity, and density of coffee extract were experimentally determined in the range of 0.49 to 0.90 (wet basis) water content and at temperatures varying from 30 to 82 degreesC. Thermal conductivity and specific heat were measured by means of the same apparatus- a cell constituted of two concentric cylinders - operating at steady and unsteady state, respectively. The thermal diffusivity was measured by the well-known Dickerson's method and density was determined by picnometry. The results obtained were used to derive mathematical models for predicting these properties as a function of concentration and temperature.